Modelling and simulations of reactor neutron noise induced by mechanical vibrations. (November 2022) - Vidal-Ferràndiz, A.; Ginestar, D.; Carreño, A.; Verdú, G.; Dokhane, A.; Verma, V.; Perin, Y.; Herb, J.; Mylonakis, A.; Demazière, C.; Vinai, P.
Highlights: This work presents four methodologies to simulate the neutron noise induced by mechanical vibrations. These methodologies employ the diffusion approximation, with and without a previous homogenization model, to simulate the neutron noise in the time and the frequency domain. All methodologies provide consistent results and can reproduce typical features of the neutron noise induced by mechanical vibrations of core components. Numerical results for mechanical vibrations of fuel assemblies and core barrel vibrations are shown. Abstract: Mechanical vibrations of core internals are among the main perturbations that induce oscillations in the neutron flux field, also known as neutron noise. In this work, different simulation models for the study of the influence of the mechanical vibrations of fuel assemblies on the neutron flux in the reactor core have been discussed. These methodologies employ the diffusion approximation, with or without a previous homogenization model, to simulate the neutron noise in the time or the frequency domain. The diffusion-based approach is expected to be less accurate in the vicinity of the vibrating fuel assemblies, but correct when considering distances larger than a few diffusion lengths away from the perturbation. All methodologies provide consistent results and can reproduce typical features of the neutron noise induced by mechanical vibrations of core components. First, FEMFFUSION can perform simulations in both the time and frequency domains. Second, CORE SIM + can be used to study various neutron noise scenarios in realistic three-dimensional reactor configurations. The third methodology is centred on using commercial codes as CASMO-5, SIMULATE-3 and SIMULATE-3K. This methodology allows time domain simulations of the neutron noise induced by different neutron noise sources in a nuclear reactor. Finally, a model for time-dependent geometry is implemented for the code system ATHLET/QUABOX-CUBBOX employing a cross-section-based approach for encoding water gap width variations at the reflector.